Sekolah Islam Terpadu sebagai Sarana Internalisasi Nilai-nilai Kepemimpinan Islam - Kristiyanto, Risky; Bunga, Nurrabia; Purwanda, Indah; Kusuma, Hendra (TSAQOFAH, 2022)
This study aims to understand how to deal with educational administrative conflicts in Madrasahs and the challenges faced in managing education in Madrasas or schools. This is so that the authors as prospective teachers can understand how to resolve conflicts in the management of education in schools which need to be understood later when becoming a teacher so that they can be understood. In this paper to collect data, the authors use descriptive research methods. Because the information in this document reflects efforts to resolve conflicts in the provision of education in madrasas or schools. Poor governance will affect the development of schools, mainly due to the declining quality of education. The factors that cause governance are the decline in science and technology due to globalization, poor school quality, planning, moderation and organization. As is happening in Indonesia today, research that has not developed consistently, as well as the impact of the Ivory-19 outbreak that has messed up my education management. Therefore, in the organization and management there must be teachers who must fulfill their duties and responsibilities in school management by prioritizing education.